Preparation method of durable amphiphobic anti-icing coating with passive radiation cooling performance

Through covalent grafting technology combined with KH560, PFAS, FS-61 and other materials, a water-based polyurethane (WPU) coating was constructed, which solved the problem of unstable anti-fouling performance of the double-spark coating, achieved the long-term stability and high anti-fouling performance of the coating, and enhanced the mechanical strength and anti-ice adhesion performance.

CN119592188APending Publication Date: 2025-03-11QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES) +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411796037.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing double-spark coating has unstable anti-fouling performance in high mechanical strength environments, and the bonding performance of traditional water-based polyurethane varnish is degraded, affecting the anti-fouling and aesthetic performance of the coating.

Method used

Through epoxy ring-opening reaction, covalent grafting with aqueous polyurethane varnish, combined with KH560, PFAS, FS-61 and other materials, a water-based polyurethane (WPU) coating with excellent mechanical properties and antifouling properties is constructed.

Benefits of technology

The long-term stability and high anti-fouling performance of the coating are achieved, the mechanical strength and anti-ice adhesion performance of the coating are enhanced, and the passive radiation cooling performance is also provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592188A_ABST
    Figure CN119592188A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating preparation, in particular to a preparation method of a durable amphiphobic anti-icing coating with passive radiation cooling performance, which comprises the following steps: S1, taking a proper amount of SiO2 nanoparticles, adding deionized water, uniformly dispersing, adding FS-61 into the deionized water, stirring, then adding KH560, stirring for 1-2 hours at 90-120 DEG C, recovering the temperature of the solution to normal temperature, filtering, washing, and drying to obtain the durable amphiphobic anti-icing coating with passive radiation cooling performance. Adding PFAS, stirring until the reaction is finished, adding polyurethane gloss oil into the reactant, uniformly stirring, adding an aziridine cross-linking agent, and continuously stirring to obtain a PFK-SiO2 dispersion liquid; and S2, uniformly spraying the amphiphobic liquid prepared in the step S1 on the surface of a base material, and curing the sprayed base material at high temperature in a drying oven to obtain the amphiphobic anti-icing coating on the surface. The waterborne polyurethane coating with excellent mechanical property and antifouling property is constructed through covalent grafting of the epoxy ring-opening reaction and the waterborne polyurethane gloss oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating preparation, and in particular to a method for preparing a durable and long-lasting amphiphobic anti-icing coating with passive radiation cooling performance. Background Art

[0002] Super-amphiphobic coatings are widely used as protective and decorative layers for various substrates such as clothing, leather, ships, building substrates, glass surfaces and ceramics. These coatings usually require excellent mechanical properties to protect the substrate from external damage (e.g., cyclic friction, bending, etc.), durability to ensure the service life of the substrate, and ensure that the substrate is resistant to corrosion from chemicals and harsh environments. Especially in some environments such as heavy oil, heavy pollution, high wear and corrosion, the practical application value of the coating is more significant.

[0003] Amphoteric particles are commonly used in conjunction with adhesives such as epoxy resins and polyurethanes because they have excellent wear resistance. Polyurethane has attracted much attention due to its excellent flexibility and weather resistance. There are two common preparation methods: The first preparation method is a two-step method, which prepares an amphoteric coating by spraying an adhesive first and then spraying amphoteric nanoparticles, but the amphoteric particles on the top layer cannot be replenished in time. The second preparation method is a one-pot method, which uses a method of blending amphoteric particles and an adhesive to achieve timely replenishment of the amphoteric particles on the top layer after wear.

[0004] Although the economic cost of polyurethane materials is relatively low and the preparation process is simple, most of the applications of polyurethane materials are solvent-based systems. The release of volatile organic compounds (VOCs) during the curing process has a serious impact on human health and environmental governance. Faced with the addition of amphiphobic materials and solvents, water-based polyurethane is diluted and its bonding performance is greatly reduced. Water-based polyurethane varnish has successfully replaced water-based polyurethane because it can ensure the bonding performance while ensuring the beauty of the coating. However, traditional water-based polyurethane varnish contains a large number of polar hydrophilic groups, which causes the fluorocarbon segments to form micelle structures and wrap inside them, greatly limiting the migration of fluorocarbon segments to the coating surface to provide anti-fouling properties. In addition, the large number of polar groups on the coating surface can easily lead to the adhesion of pollutants, hindering the development of the coating.

[0005] At present, there are two basic methods to take into account both the mechanical properties and antifouling properties of the coating. One is to increase the amount of amphiphilic particles to shield the polar hydrophilic groups, so as to reduce the surface polarity of the coating and improve the antifouling properties of the coating surface. Zhang Youfa reported a fluorinated silane-fluorocarbon surfactant-silicon dioxide (F-FS-SiO2) coating. After successfully constructing the coating by blending fluorocarbon surfactant and silicon dioxide, fluorinated silane was selected for vapor deposition, thereby successfully preparing a F-FS-SiO2 coating with amphiphilic properties. Although the hydrophilic groups were successfully blocked, they only existed on the surface of the coating. In an environment with high mechanical strength, the hydrophilic groups of the coating would be exposed again after the fluorinated silane deposited on the surface of the coating was lost, which was not conducive to the long-term stable antifouling properties of the coating. Another method is to increase the crosslinking degree of waterborne polyurethane varnish to ensure that the hydrophilic groups of the coating are consumed during the curing process. Among the crosslinkers of waterborne polyurethane varnish, aziridine crosslinkers have attracted widespread attention because they can block hydrophilic groups while significantly improving the bonding properties of the coating. Although this method can increase the crosslinking density of the coating, thereby blocking most of the hydrophilic groups on the waterborne polyurethane varnish, some amine groups will still remain in the added crosslinking agent (such as waterborne aziridine crosslinker), thus affecting the antifouling performance of the coating. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a simple and environmentally friendly preparation method. Through the epoxy ring-opening reaction and covalent grafting with waterborne polyurethane varnish, a waterborne polyurethane (WPU) coating with excellent mechanical properties and anti-fouling properties is constructed. The coating is widely used in various types of substrates such as metal substrates, clothing, ceramics and buildings.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance is provided, comprising the following steps:

[0009] S1. Take an appropriate amount of SiO2 nanoparticles and add them to deionized water for uniform dispersion, then add FS-61 and stir, then add KH560, stir at 90-120°C for 1-2h, restore the solution temperature to room temperature, continue to add PFAS and stir until the reaction is completed, then add polyurethane varnish to the reactants, stir evenly, add aziridine crosslinker, and continue stirring to obtain PFK-SiO2 dispersion; wherein the mass ratio of SiO2: KH560: FS-61: PFAS is between 600: 214: 2000: 616 and 1000: 214: 3000: 1232;

[0010] S2. The amphiphobic liquid prepared in S1 is uniformly sprayed on the surface of the substrate. After the sprayed substrate is cured at high temperature, an amphiphobic anti-icing coating is obtained on the surface.

[0011] In the present invention, KH560 (γ-glycidyloxypropyltrimethoxysilane), nano-SiO2 (silicon dioxide), PFAS (1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane), FS-61 (fluorocarbon surfactant) are covalently grafted with waterborne polyurethane varnish through epoxy ring-opening reaction to construct a waterborne polyurethane (WPU) coating with excellent mechanical properties and antifouling properties. PFAS is used as a fixing agent for FS-61, waterborne polyurethane varnish is used as an adhesive, and KH560 is used as a connecting bridge between the amphiphobic particles and the adhesive. A covalent bond and hydrogen bond combination strategy is adopted to construct a waterborne amphiphobic coating with long-term stability.

[0012] Furthermore, the diameter of the SiO2 nanoparticles in step S1 is 10 to 200 nm.

[0013] Further, in step S1, FS-61 was added and stirred for 5 minutes before adding KH560.

[0014] Furthermore, in step S2, an oven is used for curing at a temperature of 100° C. and a drying time of 2 hours.

[0015] By curing at a high temperature of 100°C in an oven, KH560 acts as a bridge to connect the amphiphobic particles and the water-based polyurethane varnish, and the fluorinated long chains migrate from the inside to the coating surface.

[0016] Further, in step S2, the substrate may be one of glass, fiber, metal, wood, leather, ceramic and plastic.

[0017] A method for preparing a durable amphiphobic anti-icing coating with passive radiation cooling performance is disclosed.

[0018] Beneficial effects of the present invention:

[0019] The present invention uses PFAS as a fixing agent of FS-61, water-based polyurethane varnish as an adhesive, KH560 as a connecting bridge between the double-repellent particles and the adhesive, and adopts a covalent bond and hydrogen bond combination strategy to construct a water-based double-repellent coating with long-term stability. After spraying on the substrate, it is dried in a constant temperature drying oven to obtain a super double-repellent surface. By changing the amount of chemical reagents, part of the fluorocarbon surfactant is fixed by covalent bonds, and the fluorocarbon surfactant is induced to tend to achieve by combining the partially deposited low surface energy fluorinated silane inducer, and the formation of a dense rough low surface energy structure successfully prevents the hydrophilic unit or other polar group molecules from being attracted back to water. The rough surface manufactured can form air pockets on the coating, thereby giving the coating anti-icing adhesion performance and delayed freezing performance. In addition, due to the rough structure of the coating surface and the properties of the coating itself, the material is given passive radiation cooling performance. The coating has the characteristics of green preparation, convenient processing and multifunctionality, and has broad application prospects in textiles, extreme environment protective clothing and building substrates.

[0020] The present invention uses γ-glycidyloxypropyltrimethoxysilane (KH560), nano-silicon dioxide (SiO2), 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane (PFAS), and fluorocarbon surfactant (FS-61) as raw materials, and covalently grafts with waterborne polyurethane varnish through epoxy ring-opening reaction to construct a waterborne polyurethane (WPU) coating with both excellent mechanical properties and antifouling properties. High-temperature curing (100°C) is essential for the coating to obtain excellent antifouling properties, which is conducive to KH560 acting as a bridge to connect the amphiphobic particles with the waterborne polyurethane varnish, and the migration of fluorine-containing long chains from the inside to the surface of the coating. Simulated polluting liquids, such as water, n-hexadecane, soybean oil, glycerol, etc., do not adhere to the surface of the coating, and can successfully clean solid pollutants on the surface of the coating, indicating that the PFK-SiO2 coating has good antifouling properties and self-cleaning properties. Due to the high crosslinking degree of aziridine and isocyanate, the PFK-SiO2 coating has high mechanical strength and antifouling properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the molecular mechanism for preparing the coating of the present invention.

[0022] Figure 2 It is the particle size distribution diagram of the PFK-SiO2 suspension in the present invention.

[0023] Figure 3 is the FTIR spectrum of the particles in the present invention.

[0024] Figure 4 It is the TG curve diagram of PFK-SiO2 in the present invention.

[0025] Figure 5It is the DSC curve diagram of PFK-SiO2 in the present invention.

[0026] Figure 6 The XPS spectrum of the coating of the present invention.

[0027] Figure 7 This is the F1s spectrum.

[0028] Figure 8 This is the Si2p spectrum diagram.

[0029] Fig. 9 This is the C1s spectrum.

[0030] Fig.10 This is the ultra-depth image of the PFK-SiO2 coating in the present invention.

[0031] Fig.11 It is a cross-sectional line diagram of the PFK-SiO2 coating in the present invention.

[0032] Fig.12 for Fig.11 Magnified image of .

[0033] Fig.13 This is a scanning electron microscope image of the PFK-SiO2 coating in the present invention.

[0034] Fig.14 This is the element analysis diagram of the surface of the PFK-SiO2 coating in the present invention.

[0035] Fig.15 This is a test diagram of the wear resistance of the PFK-SiO2 coating in the present invention.

[0036] Fig.16 This is a test diagram of the cyclic bending performance of the PFK-SiO2 coating in the present invention.

[0037] Fig.17 This is a tape adhesion test diagram of the PFK-SiO2 coating in the present invention.

[0038] Fig.18 This is a test chart of the high temperature stability of the PFK-SiO2 coating in the present invention.

[0039] Fig.19 This is a test diagram of the anti-ultraviolet performance of the PFK-SiO2 coating in the present invention.

[0040] Fig. 20 This is a long-term stability test diagram of the PFK-SiO2 coating in the present invention.

[0041] Fig.21 Schematic diagram of the repellency of the PFK-SiO2 coating of the present invention to different liquids.

[0042] Fig. 22 Graph showing the delayed freezing and ice adhesion of different coatings in the present invention.

[0043] Fig.23 This is a diagram of low-temperature water contact angles of different coatings in the present invention.

[0044] Fig.24 This is a real-time temperature diagram of the fiber fabric with PFK-SiO2 coating in the present invention.

[0045] Fig.25 It is the infrared thermal image of the coated fabric and the bare fabric in the same outdoor environment. DETAILED DESCRIPTION

[0046] In order to clearly illustrate the technical features of this solution, this solution is described below through a specific implementation method.

[0047] A method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance comprises the following steps:

[0048] S1. Take an appropriate amount of SiO2 nanoparticles with a diameter of 15 nm and add 20 mL of deionized water to evenly disperse them. Then add FS-61 and stir for 5 minutes. Then add KH560 and stir at 100°C for 2 hours. Return the solution temperature to room temperature, continue to add PFAS and stir until the reaction is completed. Then add polyurethane varnish to the reactant, stir evenly, add aziridine crosslinker, and continue stirring for 3 minutes to obtain PFK-SiO2 dispersion.

[0049] S2. The amphiphobic liquid prepared in S1 is uniformly sprayed on the surface of the substrate. The sprayed substrate is cured in an oven at a high temperature of 100° C. for 2 hours to obtain an amphiphobic anti-icing coating on the surface.

[0050] The substrate can be selected from one of glass, fiber, metal, wood, leather, ceramic and plastic.

[0051] In order to explore the influence of the dosage in the amphiphobic coating on the amphiphobic properties of the coating, the dosage of SiO2, FS-61, KH560 and PFAS were explored respectively. Among them, the amphiphobic properties of the coating can achieve better results when the mass ratio of SiO2:KH560:FS-61:PFAS is between 600:214:2000:616 and 1000:214:3000:1232.

[0052] Among them, the dosage of each component in this embodiment is: SiO2 dosage is 800 mg, FS-61 dosage is 2000 mg, KH560 dosage is 214 mg and PFAS dosage is 700 mg. The PFK-SiO2 dispersion is prepared by the above steps and simultaneously cured to obtain the double-repellent anti-icing coating described in the present invention.

[0053] As controls, three control groups including SiO2, KH560 modified silica (K-SiO2), fluorocarbon surfactant and KH560 modified silica (FK-SiO2) were prepared in parallel.

[0054] 1. Characterization of the structure of amphiphobic particles:

[0055] The PFK-SiO2 suspension prepared in step S1 was placed at room temperature for 72 hours without any stratification. The suspension was analyzed for particle size. Figure 2 As shown, the particle size distribution of the PFK-SiO2 suspension shows that the modified particle size is 280nm. Since 15nm spherical SiO2 is selected as the modified particles, the particles are full of nanopores, which further ensures that the coating is hydrophobic at the nanoscale.

[0056] To investigate the successful loading of KH560 with fluorocarbon surfactants and the successful deposition of fluorosilanes, the chemical changes before and after coating were tested by FTIR. Figure 3 As shown in the figure, the FTIR spectra of the prepared SiO2, K-SiO2, FK-SiO2, and PFK-SiO2 particles are shown in the figure. The absorption peaks of SiO2 are 812 cm -1 (Si-OH stretching), 1098cm -1 (Si-O-Si stretching), the infrared spectrum of K-SiO2 particles increases by 2877 cm-1 on the basis of SiO2. -1 (CH stretching symmetry) and 2941cm -1 (CH stretching antisymmetric) two absorption peaks, indicating the successful loading of KH560, FK-SiO2 and PFK-SiO2 have characteristic peaks of 1201cm -1 (CF stretching), indicating that the SiO2 surface is successfully loaded with fluorocarbon surfactants and fluorinated silanes.

[0057] To adapt to extreme environments, thermal stability is a property that amphiphobic particles must possess. This example measures the thermal stability of PFK-SiO2. Figure 4 As shown, the TG curves show that the thermal decomposition of PFK-SiO2 can be divided into three stages, namely water decomposition, FS-61 and PFAS decomposition, and carbonization.

[0058] Within 100℃, the mass of PFK-SiO2 decreases, indicating that there is still a small amount of water in the sample. In the second stage, the thermal decomposition temperature of PFK-SiO2 shown by the DTG curve reaches 200℃. Figure 5 The DSC curve shows that the thermal denaturation temperature of PFK-SiO2 is 120℃.

[0059] The successful modification of silica nanoparticles by low surface energy species was demonstrated by XPS. Figure 6 As shown, the main elements detected on the superamphiphobic coating are C, O, N, Si, and F.

[0060] In addition, high-resolution F1s, Si2p, and C1s spectra are shown in Figure 2. Figure 7 , Figure 8 and Fig. 9 shown. Figure 7 The peaks at 689.3 eV and 689.19 eV in the F1s spectrum are attributed to the -CF2 and -CF3 groups in FS-61 and PFAS. Figure 8 The peaks at 103.61eV and 103.55eV in the Si2p spectrum are derived from Si-C and Si-O groups. Fig. 9 In the C1s spectrum, the peaks at 294.23eV, 291.91eV, 287.11eV, 286.39eV, and 284.93eV correspond to CC, CO, C=O, -CF2, and -CF3 groups in FS-61 and PFAS, respectively. The corresponding energy dispersive X-ray spectra further verify the presence of C, O, N, Si, and F elements in the coating, and the C, O, N, Si, and F elements are evenly distributed. The hydrolysis condensation of FS-61 and PFAS verified by the high intensity of C, O, F, N, and Si elements reduces the surface energy of the substrate and contributes to the non-wetting state of the superamphiphobic coating.

[0061] 2. Characterization of PFK-SiO2 composite coating morphology:

[0062] The super depth of field image of the PFK-SiO2 coating is shown in Figure 2. Fig.10 As shown, the evenly distributed hill-like protrusion structure on the coating surface can be clearly observed. Combined with the ultra-depth of field 3D image, the height difference of the roughness of the coating surface can reach 0.43mm.

[0063] In addition, Fig.11 As shown, it can be clearly observed through the coating profile that the grooves on the coating surface are 2 mm. By enlarging the coating profile, it can be clearly observed, as shown in FIG. Fig.12 As shown, 100μm grooves are densely distributed between the 2mm grooves of the coating; since the minimum diameter of a water droplet is 1-2mm, which is much larger than the groove spacing on the coating surface, the graded roughness of the coating surface becomes a key factor in constructing a super-liquid-repellent coating.

[0064] The morphology and element distribution of the coating surface were further analyzed by scanning electron microscopy and energy dispersive spectrometer. The hilly structure can be clearly observed on the coating surface. The hilly structure of the coating is magnified. Fig.13 As shown, it can be found that the coating has densely distributed protrusions, which is consistent with the super depth of field point of view.

[0065] Analyze the coating surface elements, such as Fig.14 As shown, it was found that the elements on the coating surface were evenly distributed, and no obvious aggregation was observed. The coating surface was composed of carbon, oxygen, silicon, fluorine and nitrogen, with contents of 34.57%, 29.30%, 26.84%, 5.75% and 3.54%, respectively. The fluorine element on the coating surface became the key to constructing low surface energy. Combined with the graded roughness of the coating surface, the coating thus has good amphiphobic properties.

[0066] 3. Mechanical properties test:

[0067] Mechanical properties are the key properties of coating materials in practical applications. Polyurethane varnish and aziridine crosslinking agent can form a dense crosslinking network, so that the coating has excellent mechanical properties. Wear test, bending test and tape peeling test are used to characterize the application performance of PFK-SiO2 coating in reality.

[0068] In the wear test, a piece of cotton fabric is placed on the coating surface and a 100g weight is placed on the fabric to enhance the wear effect. One wear cycle consists of moving back and forth over a distance of 12 cm at a moving speed of 5 cm / s. The wear resistance test results of the PFK-SiO2 coating are shown in Figure 2. Fig.15 As shown, the results show that even after 1000 cycles of friction, the contact angle of the coating for water and n-hexadecane is still above 150°.

[0069] After observing the 3D imaging of the coating after cyclic friction, it was found that obvious protrusions can still be observed on the coating surface, indicating that the coating has excellent wear resistance. To verify the bending resistance of the coating, leather was selected as the bending substrate. The leather substrate was bent inward and outward once for one cycle, and 2s / time for one cycle. Fig.16 As shown, after 1000 cycles of bending, it was found that the surface contact angle of the coating to water and n-hexadecane was still maintained above 150°. By observing the ultra-depth of field 3D imaging after bending, it was found that there were no bending marks on the coating surface, showing the excellent stability and flexibility of the coating.

[0070] Then, the tape adhesion test of PFK-SiO2 coating was carried out according to ASTM standards to test the adhesion of the coating on the leather substrate. A cross-cut pattern (6*6 strips) was cut on the coating surface with a blade, and the distance between each line was about 3mm. After that, a 3-meter transparent tape was firmly pressed on the damaged surface and quickly removed by peeling. According to ASTM procedures, the loss score of the coating was used to determine the adhesion grade. The adhesion strength of the coating to the substrate was determined, such as Fig.17After the tape was adhered, there was no shedding of the coating surface, and the contact angle was still able to be maintained above 150°. In addition, through its ultra-depth image and 3D imaging, it was found that the rough structure of the coating surface was not destroyed, so the coating had the highest adhesion level of 4b.

[0071] 4. Durability test:

[0072] To evaluate the stability of the coating, the coating was tested for high temperature stability, UV resistance and long-term stability. Fig.18 As shown in the figure, the contact angle of the PFK-SiO2 coating can be maintained above 150° within the range of 200°C. When the temperature exceeds 250°C, the coating loses its superoleophobicity and oil droplets adhere to the surface of the PFK-SiO2 mixed coating. To further explore the anti-ultraviolet performance of the coating, the PFK-SiO2 coating still has excellent water and oil contact angles after long-term ultraviolet irradiation, indicating that the composite coating has high anti-ultraviolet performance, such as Fig.19 In addition, after the coating was stored at room temperature for 10 days, the contact angle of the coating surface was still able to remain above 160°, as shown in Fig. 20 As shown in Figure 2, in terms of lyophobic stability, the hydrophobic and oleophobic stability of the PFK-SiO2 coating did not decrease significantly over time.

[0073] 5. Anti-icing performance test:

[0074] To evaluate the anti-icing performance of the coating, the delayed freezing time of water droplets on the coating surface and the anti-icing adhesion test on the coating surface were measured. During the delayed freezing process, a 10 μL water droplet was placed on the coating surface at a constant temperature of -15 °C, and the delayed freezing time was recorded with a camera. For the ice adhesion test, a digital push-pull force gauge was used to push the coating with a contact area of ​​100 mm. 2 The horizontal shear force on the coating surface was measured and the shear force of ice adhesion on the coating surface was calculated by formula (1).

[0075]

[0076] Where F is the instantaneous shear force when the ice layer detaches, and S is the contact area between the ice layer and the coating surface.

[0077] The results of the study on delayed freezing and ice adhesion are as follows Fig.21As shown, the PFK-SiO2 coating has the best anti-icing performance, the freezing time of water droplets on the surface is extended to 1167s, and the adhesion force of icicles on the surface is only 17KPa. Due to the high surface roughness of the PFK-SiO2 coating, the contact area of ​​the coating surface is greatly reduced, the freezing time of water droplets on the super-hydrophobic surface is prolonged, and the adhesion of ice is significantly reduced. Compared with the bare substrate, the freezing time of PFK-SiO2 is increased by about 9 minutes. The shape of the droplets on the PFK-SiO2 coating is always spherical, while the droplets on the FK-SiO2 coating collapse from a spherical shape to a hemispherical shape. The water contact angle of the coating was further tested at low temperatures, such as Fig. 22 As shown in the figure, at 0°C, the water contact angle of the PFK-SiO2 coating remains above 150°, while the water contact angle of the FK-SiO2 coating remains at 130°. The reason for this phenomenon is that water vapor in the air frosts on the coating surface at low temperatures. The relatively dense surface of the SiO2 and K-SiO2 coatings allows the ice to form an interlocking structure with the surface roughness structure of the coating, resulting in hydrophobicity (or decreased ice-phobicity). The porous structure and multi-level roughness structure of the FK-SiO2 and PFK-SiO2 coatings with low surface energy effectively reduce the adhesion of frost on the surface and maintain the stability of the contact angle at low temperatures.

[0078] 6. Daytime radiation cooling performance test:

[0079] The passive daytime radiation cooling field measuring instrument was used to test the radiation cooling performance. During the measurement process, polyethylene film was used to cap the device and aluminum foil was used to cover the device to reduce the influence of air heat convection exchange and conductivity. The measuring device consists of a sample connected by a thermocouple and a temperature measuring device. In the passive radiation cooling experiment, the real-time temperature of the fiber fabric is as follows: Fig.23 As shown, it can be clearly observed that under direct sunlight from 12:10 to 13:00, the average cooling effect is 2°C lower than that of bare fiber fabric. Note that all test conditions remain consistent to exclude the influence of textiles on the experimental results. PFK-SiO2 coated fabric has high solar reflectivity, which reduces the heat absorption of sunlight with the greatest efficiency, and has an atmospheric window with high emissivity, which maximizes the heat radiation output.

[0080] Fig.24 The following are infrared thermal images of coated and bare fabrics in the same outdoor environment. It can be clearly observed that the temperature of the PFK-SiO2 coated fabric is much lower than that of the bare fabric and the surrounding ground. That is, PFK-SiO2 has achieved a good radiation cooling effect.

[0081] In summary, the present invention uses water-based polyurethane varnish as an adhesive, water-based aziridine as a cross-linking agent, KH560 as a bridge between the amphiphobic particles and the adhesive, PFAS-modified silica as an amphiphobic particle, and FS-61 as a solubilizer, and successfully prepares a PFK-SiO2-stabilized water-based polyurethane varnish dispersion suspension. The corresponding coating prepared by the PFK-SiO2 dispersion has high mechanical properties and antifouling properties, and can adhere to a variety of substrates. In an aqueous environment, the presence of fluorocarbon surfactants forms an outer hydrophilic micelle with fluorinated silane. After the water on the coating surface evaporates at high temperature, due to the tendency of fluorinated silane, the fluorocarbon long chain of the fluorocarbon surfactant migrates to the coating surface, giving the coating surface a low surface energy. In order to connect the amphiphobic particles and the water-based polyurethane varnish through a covalent bond, KH560 is selected as a bridge between the two. Water and n-hexadecane liquid can remove solid pollutants on the surface of the PFK-SiO2 coating. If the PFK-SiO2 coating is taken out after being immersed in simulated pollutants, the pollutants will not remain on the coating surface. In addition, the anti-icing test of the coating found that the adhesion pressure of icicles on the coating surface was only 17kPa, and the freezing time of water droplets on the coating surface was extended to 1167s, which was 555s longer than that of the bare substrate. Under sunlight, the temperature of PFK-SiO2 dropped significantly by about 2°C compared with the bare substrate.

[0082] Of course, the above description is not limited to the above examples. Technical features not described in the present invention can be achieved by or by using existing technologies, which will not be described here. The above embodiments and drawings are only used to illustrate the technical scheme of the present invention and are not limitations of the present invention. The present invention is described in detail with reference to the preferred implementation methods. Ordinary technicians in this field should understand that changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention do not depart from the purpose of the present invention, and should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance, characterized in that: The following steps are involved: S1. Take an appropriate amount of SiO2 nanoparticles and add them to deionized water for uniform dispersion, then add FS-61 and stir, then add KH560, stir at 90-120°C for 1-2h, restore the solution temperature to room temperature, continue to add PFAS and stir until the reaction is completed, then add polyurethane varnish to the reactants, stir evenly, add aziridine crosslinking agent, and continue stirring to obtain PFK-SiO2 dispersion; wherein: the mass ratio of SiO2: KH560: FS-61: PFAS is between 600: 214: 2000: 616 and 1000: 214: 3000: 1232; S2. The amphiphobic liquid prepared in S1 is evenly coated on the surface of the substrate. After the sprayed substrate is cured at high temperature, an amphiphobic anti-icing coating is obtained on the surface.

2. The method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance according to claim 1, characterized in that: The diameter of the SiO2 nanoparticles in step S1 is 10 to 200 nm.

3. The method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance according to claim 1, characterized in that: In step S1, FS-61 was added and stirred for 5 min before adding KH560.

4. The method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance according to claim 1, characterized in that: In step S2, an oven is used for curing at a temperature of 100° C. and a drying time of 2 h.

5. The method for preparing a durable and ambiphobic anti-icing coating with passive radiative cooling performance according to claim 1, characterized in that: In step S2, the substrate may be one of glass, fiber, metal, wood, leather, ceramic and plastic.

6. An amphiphobic anti-icing coating prepared by the method for preparing a durable amphiphobic anti-icing coating with passive radiation cooling performance as described in claim 1.

Citation Information

Patent Citations

  • Waterborne polyurethane super-hydrophobic coating and preparation method thereof

    CN108047916A

  • Superhydrophobic super-oleophobic coating and preparation method thereof

    CN109575769A

  • Water-based super-amphiphobic coating with good durability

    CN116285621A

  • Al2O3 / SiO2 / polyurethane super-hydrophobic coating as well as preparation method and application thereof

    CN116445068A

  • Waterborne anti-fouling polyurethane and waterborne polyurethane anti-fouling coating formed by waterborne anti-fouling polyurethane

    CN117264165A